Dynamic range enhancement in light field imaging systems - Wahab, Abdul (İstanbul Medipol Üniversitesi Fen Bilimleri Enstitüsü, 2019)
High dynamic range imaging has been an active research area in computational photography over the last two decades. The main reason is that the dynamic range of a traditional camera is typically less than the dynamic range of the environment; and this affects the performance in digital photography and machine vision applications. An emerging research area in computational photography is light field imaging. Light field (or plenoptic) of a scene can be obtained by capturing light rays from different directions separately, as opposed to the traditional imaging systems, where light rays from different directions are accumulated, losing the directional light information. Light field imaging has been of great interest due to its post-capture capabilities, including refocusing, perspective change and depth estimation. Microlens array based cameras that recently emerged have made light field acquisition process a practical task. In this study, we present a method to extract high dynamic range image from a single capture. The method uses a plenoptic camera with minor optical modification. The optical modification is an optical mask, placed in front of the main lens to increase the vignetting effect, which is the darkening of an image towards its borders due to loss of light. As a result, different parts of the dynamic range are captured with different sub-aperture images of the light field.

Yüksek dinamik aralıklı görüntüleme son yirmi yıldır hesaplamalı görüntüleme alanında aktif bir araştırma alanı olarak devam etmektedir. Bundaki temel sebep geleneksel kameraların dinamik aralığının gerçek dünyada karşılaşılabilecek dinamik aralıktan küçük olması, ve bunun da dijital fotoğrafçılık ve makine görmesi uygulamalarındaki performansı düşürmesidir. Hesaplamalı görüntülemede yükselen bir araştırma konusu da ışık alanı görüntülemedir. Işık alanı (ya da plenoptik) görüntüleme ışınların kameraya farklı yönlerde gelen ışınların ayrı ayrı kaydedilmesiyle elde edilir; diğer taraftan, geleneksel görüntüleme sistemlerinde farklı yönlerden gelen ışınlar toplanarak açısal ışık bilgisi kaybedilir. Işık alanı görüntüleme; yeniden odaklama, perspektif değiştirme, derinlik kestirme gibi çekim sonrası kabiliyetlerinden dolayı oldukça ilgi çeken bir konudur. Yakın zamanda ortaya çıkan, mikrolens dizisine dayalı kameralar ışık alanı kaydını pratik hale getirmiştir. Bu çalışmada, tek bir çekimden yüksek dinamik aralıklı görüntü elde etmeyi sağlayan bir yöntem sunuyoruz. Bu yöntem, küçük optik değişiklikler yapılmış bir plenoptik kameraya dayanmaktadır. Optik değişiklik, ana lensin önüne yerleştirilmiş, ve ışık azalmasıyla kenarlara doğru karanlıklaşmayı arttıran bir optik maskeden ibarettir. Sonuç olarak, ışık alanının farklı perspektif görüntüleri dinamik aralığın farklı kısımlarını kaydetmektedir.
Işık alanı görüntüleme sistemlerinde dinamik aralık iyileştirme
Keywords: Light Field Imaging; High Dynamic Range; Plenoptic Camera; Camera Array; Işık Alanı Görüntüleme; Yüksek Dinamik Aralık; Plenoptik Kamera; Kamera Dizisi